2004
DOI: 10.1348/135910704773891014
|View full text |Cite
|
Sign up to set email alerts
|

The role of hardiness in stress and illness: An exploration of the effect of negative affectivity and gender

Abstract: Past research into the effects of hardiness on stress and health has yielded inconsistent findings, possibly because of a failure to acknowledge the influence of variables such as negative affectivity and gender. This study examined the main, moderating and mediating effects of hardiness in a sample of 130 (50 male, 80 female) randomly selected university staff members. Controlling for negative affectivity, limited evidence was obtained for the direct effects of hardiness on stress and illness. Kobasa's (1979)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
2
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 53 publications
3
62
2
11
Order By: Relevance
“…Firstly, there are reasons to believe that the stereotypical coping patterns of men and women are not as clear cut as presented above (Tamres et al, 2002). And secondly, research have demonstrated gender differences even when no differences in coping were present (Klag & Bradley, 2004).…”
Section: Gender Differences In Hardiness Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, there are reasons to believe that the stereotypical coping patterns of men and women are not as clear cut as presented above (Tamres et al, 2002). And secondly, research have demonstrated gender differences even when no differences in coping were present (Klag & Bradley, 2004).…”
Section: Gender Differences In Hardiness Researchmentioning
confidence: 99%
“…In later studies that have included female participants, inconsistent or equivocal results have been reported. Some have found that hardiness moderates the ill effects of stress on health for men, but not for women (Benishek & Lopez, 1997;Klag & Bradley, 2004;Shepperd & Kashani, 1991), while others have found similar effects for the two sexes (King, King, Fairbank, Keane, & Adams, 1998;Robitschek & Kashubeck, 1999;Rosen, Wright, Marlowe, Bartone, & Gifford, 1999).…”
Section: Gender Differences In Hardiness Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…More neuroticism has been associated with less hardiness (Klag & Bradley, 2004) and more avoidant coping (Bolger & Zuckerman, 1995), as well as greater psychological stress (Bolger & Schilling, 1991), physical illness (Sammallahti, Holi, Komulainen, & Aalberg, 1996), and mortality (Shipley, Weiss, Der, Taylor, & Deary, 2008). Given its broad and consistent impact on important health outcomes, neuroticism was used in the current research as a measure of affectivity.…”
Section: Individual Characteristicsmentioning
confidence: 99%
“…Ouellette and DiPlacido (2001) suggest that developing hardiness is one method of promoting workers' coping strategies, as hardy individuals are reported to have a more optimistic view of the environment. Hardiness for nurses is indicated as a protective factor incorporating commitment, control and challenge that enables an individual to manage problematic situations (Klag & Bradley, 2004;Pengilly & Dowd, 2000). This controlling type of hardiness in this context is portrayed as an attribute, with Abdollahi, Abu Talib, Yaacob and Ismail (2014) describing hardiness as a mediator.…”
Section: Naomimentioning
confidence: 99%